Peran Profitabilitas Sebagai Moderasi dalam Hubungan ESG Terhadap Manajemen Laba - Nabila Faizah Az-Zahara; Lismawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Earnings management refers to the deliberate efforts by company management to choose applicable accounting standards in the preparation of financial statements with the objective of achieving specific predetermined targets such as attracting investor interest, meeting market expectations, or preserving the company's reputation among stakeholders. This study aims to examine and evaluate the impact of Environmental, Social, and Governance (ESG) factors on earnings management, as well as assess the role of profitability as a moderating variable. The research employs a quantitative approach using secondary data and applies panel data regression analysis and Moderated Regression Analysis (MRA) through the statistical software EViews 12. The population comprises manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, with a sample of 140 companies selected through a purposive sampling technique. The findings indicate that ESG significantly and negatively influences earnings management. However, profitability does not serve as a effective moderating variable in the relationship between ESG and earnings management.